The woman is subject to man on account of the weakness of her nature . . . Man is the beginning of woman…”, St Thomas of Aquinas (1225-1274), an analysis of biblical related literary works as perpetrators of women discrimination and subjugation by man: a case of John Milton ‘Paradise Lost’ (1961), ‘Samson Agonists’ (1967) and Wim Boswinkel (2003) Erina. By - Mudzingwa, Rosemary F. (Midlands State University, 2014)
This research looks at the stereotypical presentation of women in biblical related texts by John Milton and Wim Boswinkel as well as giving an account of the causes of women debasement in society, the reasons why women are accorded all sorts of negative virtues in these male-authored texts. It is noted how women are given a low profile by men and how they are at the peripheries of religious and cultural sectors. The authors of Erina, ‘Paradise Lost’, and ‘Samson Agonists’ manipulate the Bible to acquire a greater status for the man thereby relegating women to the peripheries. The way women and men are represented in biblical related texts is explored and it has been proven that there is a tendency of creating lesser privileges for the ‘Other’ who is the female countepact. The women are noted suffering silently as they tend to believe the patriarchal misinterpretations of the Bible that are paneled to suit the needs of the men leading to female passivity, docility as well subjugation by the male